Modifikasi Puzzle untuk Pemeliharaan Fungsi Kognitif pada Lansia di Wilayah DIY: Puzzle Modification for Cognitive Function Maintenance in Older Adults in DIY - Daning Widi Istianti; Eltanina Ulfameytalia Dewi (LPPM STIKES Guna Bangsa Yogyakarta, 2023)
Background: The challenge when someone enters old age is that they will experience changes in the brain function, where memory abilities will begin to decline with age. The risk factor that causes dementia is associated with a lack of activity that stimulates the brain. Dementia cannot be prevented, but there is one way that can be done for the maintenance of cognitive function in the older adults, by compiling specially designed puzzles. Purpose: To determine the effect of puzzle modification on the maintenance of cognitive function in the older adults. Methods: A quasi-experimental study with a one-group pre-test and post-test approach involving 60 older adult respondents using a cluster sampling technique. The intervention group received treatment by giving puzzles twice a week for two consecutive weeks. The MoCA-Ina instrument was used to see the cognitive function of the older adults. Data analysis was carried out with SPSS using the Wilcoxon Signed Rank Test. Results: There is an effect on the intervention group compared to the control group with Asymp. Sig. 2-tailed < 0.05. Conclusion: Modification of the puzzle can be applied to the maintenance of cognitive function in the older adults. The results of the study are expected to be used to assist families, cadres, and nurses in maintaining cognitive function in the elderly, although there must be assistance at the time of intervention. The puzzle modifications that have been made can be further developed in digitalization so that they can be accessed by all elderly people in the world.